Gender-related Disparities of Percutaneous Coronary Interventions in ST-elevation Myocardial Infarction: A Retrospective Chart Review of 500 Patients. Issue 2 (27th July 2020) - Sleiman, Elsa; Hosry, Jeff; Caruana, Lisa; Schwartz, Moishe; Boutros, Karam; Tabet, Rabih; Salmane, Chadi; Kandov, Ruben; Royzman, Roman; Tamburrino, Frank; Lafferty, James
Abstract : Door-to-balloon (DTB) time of primary percutaneous coronary intervention in ST-elevation myocardial infarction (STEMI) is a predictive indicator of outcomes and mortality. Traditional gender-related differences that existed in the provision of DTB in STEMI had been allegedly improving until recent controversial data showed re-emergence of longer DTB in females. The objective of our study was to compare circadian disparities in percutaneous coronary intervention for STEMI according to gender in our institution. We compared DTB and symptom-to-balloon (STB) as well as mortality outcomes in a registry of 514 patients. We studied 117 females and 397 males. Baseline characteristics and cardiovascular risk factors were similar among both populations. Men used more self-transportation (51% vs. 38%) compared with women. Both had similar DTB median times: males, 63 (47–79) min; and females, 61 (44–76) min. In addition, STB median times were also similar: males, 155 (116–264) min; and females, 165 (115–261) min. Mortality outcomes at 1 month were comparable at 3% in males versus 0.9% in females ( P = 0.164). In a review of a tertiary care center in New York, we observed no gender differences in DTB and STB, endorsing the role of emergency medical service transportation in eliminating disparities.